Review on Plants Used in Siddha Formulation Vatha Siletpana Sura Kudineer for the Management of Viral Fever (International Journal of Ayurveda and Pharma Research, 2023)
Siddhars said about various diseases and the treatment methods with herbs, minerals and animal products. In Siddha literatures viral fevers can be compared to Vatha Kapha Suram and therefore decoction for this Suram is taken from classical Siddha text book and the ingredients are searched for pharmacological activity and toxicity study from 118 published journal papers from Pubmed, Scopus, Google Scholar, Research Gate and Science Direct. Collected data is entered in MS excel and analysed using RFC score. All together there are 51 pharmacological activities are published for these nine ingredients. In which Anti-inflammatory has RFC=1, other properties like antipyretic, anti-tussive, bronchodialator, anti-asthmatic, analgesic, neuro-regenerative, neuroprotective, anti-diarrhoeal, anti-emetic, neuroprotective, analgesic, sedative has more than 0.55 RFC score. More than this cardioprotective, renoprotective, hepatoprotective, and other protective properties are present in more than 50% of ingredients. In toxicity studies no toxic effects are seen in in vivo studies for the ingredients The Suvai, Thanmai, Pirivu, in Siddha aspect, of these ingredients can highly reduces Vatha and Kapha disorders. Therefore, the decoction shows significant pharmacological activity for the sign and symptoms of viral infections.